(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is a common disease and progession over time. It is the third leading cause of death in the world. Current treatment goals are to reduce the risk of exacerbations, reduce symptoms and slow disease progression. Assessing the patient for treatable traits is the current treatment approach. Objective: Describing the characteristics, treatment response and related factors of outpatients with COPD managed at the National Lung Hospital from 2021 to 2022. Methods: Descriptive study, conducted on 223 patients diagnosed with COPD, outpatient management at the National Lung Hospital from 1/2022 to 1/2023. Results: Mean age of the patients was 67.63± 8.60 years, 22.9% of patients had a history of pulmonary tuberculosis, and 65,5% of patients had comorbid diseases, of which hypertension is the most common disease with a 18.8%. Patients have clinical improvement after treatment. mMRC scores before and after treatment were 2.24±0.46 and 2.11±0.48, the average number of exacerbations before treatment was 2.06±1.44 exacerbations/year, after treatment was 1.26±1.12 exacerbations/year, the difference is statistically significant. The average FEV1 decline after 12 months is 36.46±135.06 ml per year. Patients with a history of pulmonary tuberculosis, blood BCAT ≥ 300/μl, ≥ 2 exacerbations in the previous year, ≥ 2 co-morbidities are risk of FEV1 greater decline but non-significance. Conclusion: Patients with COPD often have many comorbidities, commonly comorbidities are high blood pressure (18.8%), lipid metabolism disorders (15.7%); Patients have clinical symptom improvement and number of exacerbations per year after treatment. Patients with a history of pulmonary tuberculosis, blood BCAT ≥ 300/μl, ≥ 2 exacerbations in the previous year, ≥ 2 co-morbidities, are at increased risk of FEV1 greater decline.